Social capital across the life course and functional somatic symptoms in mid-adulthood. Issue 7 (November 2014) - Jonsson, Frida; Hammarström, Anne; Gustafsson, Per E.
Aim: To examine social capital across life and functional somatic symptoms in middle-age, according to life-course models of cumulative risk and sensitive periods. Methods: Data from the 26-year prospective study the Northern Swedish Cohort enabled complete case analyses on 940 individuals (451 women and 489 men) participating in questionnaire surveys at ages 16, 21, 30 and 42. Social capital was operationalized at the individual level, comprising items on social participation, social influence and social support. Functional somatic symptoms were a summary measure of self-reported physical symptoms, palpitation and sleeping difficulties occuring during the 12 months prior to the data collection. Linear regression was used as the main statistical method, examining the relationship between functional somatic symptoms at age 42 and social capital across life. Results: Lower levels of social capital accumulated over the life course were associated with higher levels of functional somatic symptoms at age 42, for both women and men. Social capital was, especially among adolescent men, related to functional somatic symptoms at age 42, independently of social capital later in life and baseline material circumstances. Conclusions: The health impact of poor social capital may be due to accumulation across the life course and to adolescence being a particularly sensitive period. It is relevant for preventive work to acknowledge effects of social capital throughout life.